Optimal threshold of postintervention minimum stent area to predict in‐stent restenosis in small coronary arteries: An optical coherence tomography analysis. Issue 1 (13th August 2015) - Matsuo, Yoshiki; Kubo, Takashi; Aoki, Hiroshi; Satogami, Keisuke; Ino, Yasushi; Kitabata, Hironori; Taruya, Akira; Nishiguchi, Tsuyoshi; Teraguchi, Ikuko; Shimamura, Kunihiro; Shiono, Yasutsugu; Orii, Makoto; et al.
Abstract : Objectives: The aim of this study was to determine the best threshold of postintervention minimum stent area (MSA) assessed by optical coherence tomography (OCT) to predict long‐term in‐stent restenosis (ISR) for 2.5 mm‐diameter everolimus‐eluting stents (EES). Background: Percutaneous coronary intervention (PCI) for small coronary arteries remains challenging. Stent underexpansion is a strong predictor of late ISR. Methods: We performed a retrospective analysis of 69 lesions in 69 patients undergoing PCI with 2.5 mm‐diameter stents using OCT for the assessment of postintervention MSA and subsequent 9‐month angiographic follow‐up. Results: The rates of angiographic ISR and target lesion revascularization were 7.2% and 1.4%. The postintervention OCT‐MSA of EES < 3.5 mm 2 for predicting ISR yielded a sensitivity of 80%, specificity of 71%, positive predictive value of 18%, and negative predictive value of 98%. There was a marginally significant trend between increasing MSA quartiles and decreasing ISR rate ( P for trend = 0.07). Conclusions: Postintervention OCT‐MSA of 3.5 mm 2 best predicted 9‐month ISR following PCI with 2.5‐mm‐diameter EES. Further large, prospective, observational studies are warranted that validate this result. © 2015 Wiley Periodicals, Inc.